Leiomyosarcoma of the Skin and Subcutaneous Tissue in a Nellore Cow - Pires, Ana Paula de Castro; Barbosa, José Diomedes; Costa, Samay Zillmann Rocha; Oliveira, Mariana Correia; de Oliveira, Carlos Magno Chaves; Brito, Marilene de Farias (Acta Scientiae Veterinariae, 2017)
Background: Leyomiosarcomas are uncommon malignant smooth muscle tumors of hollow organs. Bovine leyomiosarcomas have been described in several sites, but smooth muscle tumors that arise from the skin are rare in domestic animals. These neoplasms may show variable histologic features depending on their grade of differentiation; therefore, diagnostic tools as special stain, electron microscopy and immunohistochemistry are essential for the definitive diagnosis. Due to the lack of reports of skin leyomiosarcomas in cattle, we described the occurrence of a leyomiosarcoma in the skin and subcutaneous tissue of a Nellore cow. Case: A 10-year-old Zebu Nellore cow was admitted at the Veterinary Diagnosis Center (CEDIVET) of Pará Federal University (UFPA), Brazil, to investigate a tumor on the hip. At clinical examination the cow showed a decreased appetite and weight loss. Due to the bad prognosis the veterinarian recommended euthanasia. Representative tissue samples were submitted for histopathological and immunohistochemistry evaluation at the Department of Pathology of the Federal Rural University of Rio de Janeiro (UFRRJ). The slides were stained by Hematoxylin and Eosin (HE), Masson’s trichrome and Van Gieson stains and submitted for immunohistochemistry with primary antibodies vimentin, troponin C, smooth muscle alpha actin and desmin. Grossly, the tumor appeared as a multilobular, ulcerated and firm 30 cm diameter mass with black and hemorrhagic areas on the surface. The mass was scattered throughout the subcutaneous tissue and infiltrated the adjacent muscle. On light microscopy, the neoplasm consisted of a non-encapsulated proliferation into the derma, composed of highly pleomorphic spindle to round cells arranged in broad interlacing fascicles and small islands. Metastatic lesions were found in the lungs and local lymph nodes. Masson’s trichrome stain revealed collagen production and Van Gieson stains was inconsistent. Immunohistochemically, the neoplastic cells expressed vimentin diffusely and smooth Alfa actin in 10% of the cells. Desmin and troponin C failed to express immunoreactivity. Discussion: The histological, histochemical and immunohistochemical features of the neoplasm were consistent with a leiyomiosarcoma of the skin and subcutaneous tissue. Leiomyosarcomas are uncommon in farm animals and most of them arise from the female genital tract, especially in the vagina and within the uterus. The majority of smooth muscle tumors of the skin are benign; however, we described here a neoplasm that displayed clear signs of malignancy. Due to the high grade of differentiation, Van-Gieson stain failed to determine the origin of the neoplasm. Many sarcomas have resembling histologic features and busually display interlacing bundles of spindle shaped cells, similar to the pattern described in the present tumor. Therefore, immunohistochemistry stain with vimetin and smooth alpha actin was essential for the definitive diagnosis. We identified metastatic lesions in the local lymph nodes and lungs. This tumor tends to develop slowly and metastasize late. These findings underline the importance of diagnostic tools, such as immunohistochemistry and special stains to guide the pathologist and to establish the diagnosis of bovine smooth muscle tumors. Consequently, an association of histochemical and immunohistochemical procedures is indispensable to guide the pathologist for the establishment of the diagnosis of bovine smooth muscle tumors.